Plastic debris pollution on recreational beaches: A Malaysian case study - Shahul Hamid, F.; Ibrahim, N.A.A. (2014)
The significance of marine debris presence particularly plastic in marine ecosystem calls for proper monitoring strategies to establish a solid foundation for mitigation measures. The objectives of this paper are to study plastic debris distribution while correlating it to the level of awareness on marine pollution among beach users. It is aimed to investigate the impacts of tourism activities and the abundance of plastic debris on the beach. To quantify plastic debris on the beach, five points with duplicates were taken for three consecutive months. These sand samples were sieved through 1.00mm, 2.80mm and 4.7mm apertures. On the other hand, questionnaires were distributed to 625 beach users to study the awareness on issues related to marine pollution. Results indicated that the most crowded site accumulated the highest number of plastic debris (59 items), ranging between 1.00mm to 2.8mm (48% of the total weight of plastic). Debris sizing 4.75mm and more only contributed 41% of the total weight. Questionnaires data revealed that 2.4% of the respondents admitted to leave waste on the beach particularly if no garbage bins are provided, while the majority (92%) collect and throw the waste elsewhere. As for the cause of polluted beaches, 56% believed it is due to the indifferent attitude of the beach users that 20% of the respondents felt that stricter law should be enforced. It can be concluded that the number of plastic debris is highly influenced by the number of beach users. On the other hand, though it is lower in weight, smaller debris makes the largest number of items on the beach. While public believe that more stringent enforcement should be in place, an efficient waste management is also vital to prevent further detrimental impacts of plastic debris to the marine ecosystem.